Pro-Environmental Behaviour in Tourism: A Systematic Literature Review and Future Research Directions - Prawira, Mega Fitriani Adiwarna; Ramadhani, Iqlima; Audita, Vanda Nirma; Andrianto, Ronal; Prawira, Aura Bulan Andhara (Politeknik Negeri Bandung, 2024)
As one of the largest global economic sectors, tourism significantly contributes to economic and social development. However, it is also a leading cause of environmental degradation, including ecosystem disruption, carbon emissions, and resource exploitation. Tourists ' pro-environmental behavior (PEB) is crucial in mitigating tourism's adverse effects through sustainable actions like responsible waste management and green transportation. This study employs a Systematic Literature Review (SLR) method to synthesize research on PEB in tourism from 2013 to 2023. Drawing from 24 peer-reviewed articles from the Scopus database, the review identifies key themes: intrinsic and extrinsic behavioral drivers, the transformative role of technology, emotional engagement, organizational and community-level factors, and the unique challenges of rural tourism. The findings reveal that intrinsic factors, such as personal norms and moral obligations, are foundational drivers of PEB, while extrinsic factors, including environmental policies and supportive infrastructure, enable sustainable actions. Technology, particularly AI, social media, blockchain, and augmented reality, emerges as a dynamic antecedent, enhancing transparency and decision-making in sustainable tourism practices. Emotional engagement, such as awe and attachment to destinations, amplifies tourists' long-term commitments to sustainability. However, significant research gaps remain, including the need for longitudinal studies, geographic diversity, and cross-cultural analyses. The study proposes a conceptual model integrating these factors with sociocultural contexts, moderating their effectiveness. This model offers theoretical insights and practical implications for policymakers, destination managers, and researchers. The tourism sector can promote PEB and advance sustainable practices globally by addressing identified gaps and adopting innovative strategies.